Agronomic and edaphoclimatic characterization high altitude vineyards (Revista de Ciências Agroveterinárias, 2016)
The objective of this research was to perform the agronomic and edaphoclimatic characterization of vineyards and to determine cultivation trends for the main varieties employed in the production of high altitude fine wines in Santa Catarina State, Brazil. High altitude vineyards were considered those vineyards located 900 m above sea level and vineyards belonging to members of the Santa Catarina Association of Altitude Fine Wines located below 900 m altitude. To assess cultivation trends, the vineyards were geo-referenced, following the Embrapa Uva e Vinho guidelines. To perform the edaphoclimatic characterization, the vineyard polygons were overlaid with physiographic, climatic and soil maps in a Geographic Information System. The characterization of the high altitude vineyards was based on planted area. The varieties with greatest areas were Cabernet Sauvignon (37.9%), Merlot (14.5%) Chardonnay (8.0%) and Sauvignon Blanc (7.5%). From 2009 to 2013 vineyards with C. Sauvignon were replaced for white varieties and for Pinot Noir, especially in altitudes over 1,100 m. A trend in the use of white varieties and Pinot Noir in new vineyards was identified, but the main trend was the increase of experimental areas, with additional 60 varieties of red and white grapes. In relation to physiography, the norm of the Acavitis requires that the vineyards of their associates be located above 900 m of altitude. However, vineyards were found at altitudes ranging from 675 m to 1,452 m, with 64.6% of the area found between altitudes ranging from 1,100 to 1,300 m above sea level. The annual rainfall was 240% higher than the values considered optimal described in the literature for high altitude vineyards. The average annual temperature ranged between 12 °C and 18 °C and both the temperature range as the annual hours of sunshine were considered sufficient to complete the cycle of all varieties.
Keywords: Vineyard geo-referencing; high altitude wines; viticulture; Brazilian wines.